The Role of Metacognitive and Socio-Affective Strategies in Shaping Communicative Competence among EFL University Students - Juwita Boneka Sinaga; Ribut Wahyu Eriyanti; Ria Arista Asih; Akhsanul In'am; Masduki Masduki; Suryo Hartanto; Jenny Rose O Tumacder (Jurnal Pemberdayaan Masyarakat, 2025)
In the context of English as a Foreign Language (EFL) education, communicative competence remains a crucial goal for higher education students. However, the roles of learning strategies—particularly metacognitive and socio-affective strategies in shaping communicative competence are still underexplored. This study aims to examine the predictive relationship between students’ use of metacognitive and socio-affective strategies and their overall communicative competence. Employing a quantitative approach with multiple regression analysis, data were collected from 120 EFL university students using standardized questionnaires. The findings revealed that socio-affective strategies significantly predicted students’ communicative competence, while metacognitive strategies did not demonstrate a significant effect. The results suggest that emotional regulation, interpersonal interaction, and social support are essential components in enhancing students’ ability to communicate effectively in English. This research contributes to applied linguistics and EFL pedagogy by emphasizing the importance of socio-affective dimensions in language learning and advocating for strategy-based instruction in classrooms. In terms of practical contribution, the study offers insights for language educators and curriculum developers to design more holistic and student-centered teaching strategies that promote not only linguistic knowledge but also emotional engagement and communicative confidence among students.